Effect of alumina nanofiller on the viscosity and electrical conductivity of glass-based seals for solid oxide fuel cells - Lee, Dong Bok; Park, Sung-Min; Jo, Sung-Mi; Kim, Eun-Jeong; Park, Sung; Lee, Jae Chun; Lee, Hae-Weon; Lee, Jong-Ho (SPRINGER, 2014)
Use of alumina nanofiller to strengthen the structure of the sealing glass used for solid oxide fuel cells (SOFCs) has been investigated by measurement of fracture strength, viscosity, and electrical conductivity at elevated temperatures. The electrical conductivity and viscosity of two glass-based seals for SOFCs were compared. Measurement of electrical conductivity and viscosity of the glass-based seals over the temperature range 400-600 A degrees C showed that addition of 10 % nano-sized alumina powder to the sealing glass increased both the high-temperature electrical conductivity and viscosity of the sintered glass matrix. The higher conductivity and viscosity of glass composites containing alumina nanofiller were attributed to formation of bonds with bridging oxygen by partial dissolution of the alumina nanofiller in the sealing glass. Infrared spectroscopy and X-ray diffraction analysis were conducted to confirm this conclusion. Strengthening of the sealing glass structure to improve long-term durability may be possible by using glass composites containing alumina nanofiller.
Keywords: COMPOSITES; BEHAVIOR